PSYCHOLOGICAL MECHANISM ON PUBLIC ORGANIZATION - MEUTIA KARUNIA DEWI (Jurnal Akuntansi, Manajemen dan Ekonomi, 2019)
Public sector motivation (PSM) becomes a strategic issue along with the decadence of the classic bureaucracy era. This concept focuses on components that can psychologically encourage positive attitudes and behavior of public employees. In order to find the main values ​​and motivations, public employees need to consider organizational characteristics related to leadership and employees perceptions of the organization. This study aims to analyze the influence of transformational leadership and employees positive perceptions on the organization to PSM. The study was conducted on Government employees in Central Java using survey methods. Using regression analysis, the results of this study contribute to give empirical findings regarding the relationship of organizational characteristics to PSM.